ECONOMIC ANALYSIS ON MARKET POTENTIAL OF ETHIOPIAN RURAL MARKET - Shiferaw-Mitiku T.; Shemelis-Zewdie Mersha; Ushadevi K.N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2014)
Ethiopia has taken great strides to reduce poverty and increase the welfare of its largely rural, agricultural-based population. Ethiopia, a country with rural based economy mainly from Agriculture sector which contributed with the range of 42.5 percent to 67.25 percent of the GDP for the past two decades (1990-2012). Similarly, the percentage of Rural population against the total population of the country accounts a larger coverage; with 87.38 percent for the year 1990, 85.26percent during 2000 and 82.46 percent for the year 2013. There is a steadfast growth in the total rural population from 41 million in 1990 and reached to 77.59 million in 2013 with average annual percentage growth rate of 2.8 for the past twenty three years. Very importantly, the major exportable products of the country is generated from the marketing of Agricultural produce such as coffee, khat, live animals, oilseeds, flowers, sesame, and also leather products. Above all, the consumption pattern and preference of rural consumer is changing due to the dynamic nature of marketing. However, marketers are failing to reach this largest target market of the population. This is mainly because, marketers are focusing on designing a product for urban market and when it becomes obsolete, it moves to the rural market. Indeed, it is unethical to override the marketing preference of the rural consumer. Recognizing the marketing requirements of the majority of the population would helps to bring a vibrant economic impact in the development of the nation. The present paper highlighted the major challenges and opportunities of Rural Marketing in Ethiopia, identified ways to explore the untapped Ethiopian Rural Market and identified possible recommendations and policy implications that would help to bring an improved development in the rural Ethiopia. Accordingly, the present article seeks the attention of Policy makers, Investors, Higher education curriculum developers and marketers to this vital area of development, to respond the call of the untapped Ethiopian Rural Market.